Les miserables eaudiobook - Hugo, Victor (Recorded Books Inc., 2011)
One of the great classics of world literature and the inspiration for the most beloved stage musical of all time, Les MisErables is legendary author Victor Hugo's masterpiece. This extraordinary English version by renowned translator Julie Rose captures all the majesty and brilliance of Hugo's work. Here is the timeless story of the quintessential hunted man-Jean Valjean-and the injustices, violence, and social inequalities that torment him. "Rich and gorgeous. This is the [translation] to read."-Times (London)